2013
DOI: 10.1111/jasp.12099
|View full text |Cite
|
Sign up to set email alerts
|

Influence of self‐esteem, locus of control, and organizational climate on psychological empowerment in a sample of Chinese teachers

Abstract: This study examined the effects of locus of control, self-esteem, and organizational climate on psychological empowerment in a sample of Chinese teachers. Participants were 1,272 Chinese teachers (460 men and 821 women) residing in six provinces in China. Results indicated that self-esteem was a positive predictor of psychological empowerment. Several dimensions of organizational climate, namely professional communication, decision-making, appraisal and recognition, supportive leadership, and professional grow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
25
0
6

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(33 citation statements)
references
References 36 publications
(46 reference statements)
2
25
0
6
Order By: Relevance
“…These findings are congruent with Tunde and Onabanjo's (2013) conclusions about 200 teachers from Lagos where they discovered that teachers whose self-esteem is higher are less likely to suffer burn-out. Wang et al (2013) found that self-esteem was a positive predicator of psychological empowerment in 1,273 Chinese teachers. Very few studies were found in the extant literature linking collective self-esteem and educators.…”
Section: Collective Self-esteemmentioning
confidence: 99%
“…These findings are congruent with Tunde and Onabanjo's (2013) conclusions about 200 teachers from Lagos where they discovered that teachers whose self-esteem is higher are less likely to suffer burn-out. Wang et al (2013) found that self-esteem was a positive predicator of psychological empowerment in 1,273 Chinese teachers. Very few studies were found in the extant literature linking collective self-esteem and educators.…”
Section: Collective Self-esteemmentioning
confidence: 99%
“…In her research, Moura, Orgambídez-Ramos and de Jesus (2015) asserted that psychological connection of the employees with their work needs to be the prime concern for the organizations to bring out effective performance. Moreover, both engagement and psychological empowerment enhance the satisfaction level of the employees as well as their committment and task performance (Seibert, Wang andCourtright (2011), Maslach andLeiter, 2008).…”
mentioning
confidence: 99%
“…Individually, they are unique where one concentrates only for work development perspective and the other addresses the organization holistically. Apart from that, there is a lack of knowledge development regarding these variables in an Asian context (Wang, Zhang and Jackson, 2013). Researchers identified the constructs cannot be globally generalized except in the work domain (Spritzer, 1995).…”
mentioning
confidence: 99%
“…Hence, magnifying empowerment as an organisational climate construct can enhance the understanding of employee empowerment. Organisational climate has been defined as 'a set of measurable properties of the work environment, perceived directly or indirectly by employees'; it is assumed that organisational climate affects employee motivation and behaviour in the organisation (Wang, Zhang, & Jackson, 2013, p. 1430.…”
Section: Impact Of Culture On Empowermentmentioning
confidence: 99%